Национально-культурная самоидентификация в русскоязычной художественной литературе XXI века: лингвистический аспект (на материале романа Е. Водолазкина «Лавр») - ЛАППО, МАРИНА АЛЕКСАНДРОВНА (SlavVaria, 2021)
National-cultural self-identification in Russian-language fiction of the XXI century: a linguistic aspect (on the material of E. Vodolazkin’s novel “Laurus”). The paper aims to analyze the linguistic methods of constructing ethnocultural identity in the space of E. Vodolazkin’s novel “Laurus”. The author describes the linguistic identity of the heroes and the narrator, based on the combination of elements of the Old Russian language and various stylistic layers of the modern Russian language, and the significant opposition of the Middle Ages / Ancient Russia. It is proved that the interpretation of national and cultural self-identification in a literary text can become a tool for identifying its semantic dominant.